The Conceptual Confusion of Teaching Quality and Teacher Quality, and a Clarity Pursuit - Awuradjoa Aidoo; Luo Shengquan (International Journal of Asian Education, 2021)
This study aimed to establish and understand the conceptual confusion between teaching quality and teacher quality and design a path for their distinction. The study conducted searches on ERIC, ScienceDirect, JSTOR, Sage Journals, Sage Knowledge, Web of Science, and random Google search engine utilization for teaching quality, teacher quality, differences between teacher quality and teaching quality, and conceptual confusion. The study applied Gidden's structuration theory to foster clarity development amid conceptual confusion. The study also highlighted the relevance of the concepts' distinction, inter-relatability, and connecting boundaries and was guided by the research questions: how can the concepts be distinguished from each other? How can the conceptual confusion between them be cleared? The study discovered pathways to understand the conceptual differences through deconstruction, classification, and relationship and role pairing. The study discovered: differences do exist between the two concepts in content and realization; some of the relationships between the concepts serve as their explicit conceptual differentiators: some were discovered to possess purposes of linking the concepts, while some detached the concepts; the existing relationships also unveiled the deriving roles of the concepts on each other and in practice; and proposed a framework for their distinction and clarification. Implications for practice include enablement of professional development needs identification for teachers; clarification of areas for leadership coaching and mentoring of teachers; self-awareness creation for teachers in seeking professional growth; student achievement; school improvement and action research enhancement.